2018
DOI: 10.1038/s41467-018-03581-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory gain modulation of defense behaviors by zona incerta

Abstract: Zona incerta (ZI) is a functionally mysterious subthalamic nucleus containing mostly inhibitory neurons. Here, we discover that GABAergic neurons in the rostral sector of ZI (ZIr) directly innervate excitatory but not inhibitory neurons in the dorsolateral and ventrolateral compartments of periaqueductal gray (PAG), which can drive flight and freezing behaviors respectively. Optogenetic activation of ZIr neurons or their projections to PAG reduces both sound-induced innate flight response and conditioned freez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
109
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 58 publications
15
109
2
2
Order By: Relevance
“…Currently, the database contains projection neurons primarily from the hypothalamus (Figure 3 With this resource we were able to discover novel projection classes in diverse brain areas. For example, zona incerta (ZI) is a brain region with poorly defined circuits that have been associated with defensive behavior (Chou et al, 2018), appetite (Zhang and van den Pol, 2017), and motor functions (Kim et al, 1992). ZI neurons project to numerous regions within the medulla, midbrain, and thalamus (Sita et al, 2007), but little is known about whether they form projection classes to subsets of these brain regions.…”
Section: Semi-automated Reconstruction Of Complete Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the database contains projection neurons primarily from the hypothalamus (Figure 3 With this resource we were able to discover novel projection classes in diverse brain areas. For example, zona incerta (ZI) is a brain region with poorly defined circuits that have been associated with defensive behavior (Chou et al, 2018), appetite (Zhang and van den Pol, 2017), and motor functions (Kim et al, 1992). ZI neurons project to numerous regions within the medulla, midbrain, and thalamus (Sita et al, 2007), but little is known about whether they form projection classes to subsets of these brain regions.…”
Section: Semi-automated Reconstruction Of Complete Neuronsmentioning
confidence: 99%
“…We found that rostral ZI neurons are anatomically diverse but could be divided into cells that projected to the periaqueductal grey (PAG) and medulla ( Figure 3; n = 4/12 cells), PAG and superior colliculus (SC; n = 4/12), or thalamus (4/12 cells). Two of these cell groups share a projection to the PAG, which is associated with defense and escape behaviors (Chou et al, 2018). PAG and medulla projecting neurons had dense projections to the pontine reticular nucleus, which is involved in movement generation, whereas the other PAG projecting subset innervated SC, a brain area thought to be critical for sensory-guided orientation of movements (Kim, Gregory et al 1992 groups of ZI projection patterns appear to map onto different behavioral functions.…”
Section: Semi-automated Reconstruction Of Complete Neuronsmentioning
confidence: 99%
“…GABAergic cells in the ZI have been implicated in defensive responses like freezing and avoidance as well as in retrieval of aversive memories (29,30). We tested whether targeted stimulation GABAergic cells in the ZI can reduce fear generalization (Fig.…”
Section: Increasing Activity Of Gabaergic Cells In the Zi Reduces Feamentioning
confidence: 99%
“…At the level of the thalamus, studies have demonstrated that the auditory thalamus influences fear generalization (25,26) and that the paraventricular thalamus influences fear conditioning and fear memory retrieval (27,28). Most recently, the zona incerta (ZI), a sub-thalamic region, has received attention for its role in modulating defensive responses and retrieval of fear-related memories (29,30). Notably, studies in rodents have highlighted that the ZI influences sensory discrimination (31,32) and that stimulation of the ZI in humans facilitates discrimination of fearful from non-fearful stimuli (33).…”
Section: Introductionmentioning
confidence: 99%
“…There is at least a foundational basis for dopamine-and GABA-mediated transmission in the PVT, but it remains to be determined if these chemical messengers would mediate the same behavioral roles at the PVT or elsewhere. For instance, another ZI GABA pathway targets the periaqueductal gray (PAG), and is implicated in the control of flight and freezing responses (Chou et al, 2018). A neuroanatomical tracing study showed ZI TH-ir projections to the PAG in rats (Messanvi et al, 2013) allowing for the possibility of a role for dopamine in mediating defensive behaviors.…”
Section: Discussionmentioning
confidence: 99%